Differential impact of the Great Recession on foreign and domestic firms in China: Did processing trade play a role in export performance?. Issue 4 (19th May 2021) - Munasib, Abdul; Roy, Devesh; Tian, Xi
Abstract : Using firm-level transaction records from the proprietary Chinese Customs data we estimate differential impacts of the Great Recession (GR) of 2008–2009 on exports of private domestic firms (PDFs) and foreign invested firms (FIFs). We exploit the longitudinal nature of the data spanning almost a decade (2003–2011), as well as product level details available in the customs data, to establish the links. We identify processing trade intensity as one possible mechanism behind the change in exports due to the GR, as well as the differentiated recovery across firm types in its aftermath. Prior to the GR, compared to the PDFs, the FIFs not only accounted for the larger share of China's exports but were also relatively more involved with processing trade. Subsequently, it seems that the firms with greater processing trade intensity were affected more due to GR. We argue that in a comparative sense, processing trade of the FIFs captures the transmission of the negative demand shocks of the GR.